My home, my school, my computer: the rhetoric of everyday teaching during the 2020 pandemic (Revista Contexto & Educação, 2026)
The article examines the rhetoric of everyday teaching during the 2020 pandemic, as described in the lyrics of the song Samba do Ensino Remoto, to identify the social representations of teaching work in that context. In that pandemic year, the abrupt replacement of face-to-face classes with remote teaching reconfigured teaching practices and challenged the school community. The song describes the unprecedented school routine from the teachers’ perspective, revealing the tensions of that period. In Social Representations, lay knowledge, elaborated in common sense, serves as raw material to expose the positions of social actors in situated contexts. The metaphor is the figure of thought, as affirmed by Mazzotti (2003), that condenses and coordinates the discourses that engender social representations. From this perspective, metaphor constitutes the point of confluence of the theories that underpin this article. Thus, the analysis brings together the Theory of Argumentation proposed by Perelman and Olbrechts-Tyteca (1996), which recovers Aristotelian rhetoric to reason about values, and Lakoff and Johnson’s Conceptual Metaphors (2002) to identify the social representations of teaching work by teachers who teach in schools. As a result, the container metaphor emerges as the model or figurative core of the social representations of teaching work by teachers in the pandemic context. The computer is the container that replaces the physical space of the school, operating as a cell that ambiguously imprisons and frees, as it is the possible means of maintaining the process of schooling.
Keywords: remote education; K-12 education in the pandemic; social representations; theory of argumentation; conceptual metaphor